Optimizing Village Governance: A Siyasah Dusturiyah Perspective on Law No. 3/2024 - Mega Puspita; Khairul Umami (Ministry of Home Affairs, 2025)
This article examines Law No. 3 of 2024 concerning Villages, an amendment to Law No. 6 of 2014, from the perspective of siyasah dusturiyah (Islamic constitutional politics), with particular emphasis on exploring opportunities and challenges in optimizing village governance. Using a normative legal method, this study analyzes how the core principles of siyasah dusturiyah justice (al-adl), transparency and accountability (al-masuliyyah wa al-muhasabah), consultation (as-shura), and anti-corruption (mubarazah al-fasad) are reflected in the revised law. Findings indicate that Law No. 3/2024 offers promising opportunities to promote participatory, transparent, and fair village governance, particularly through strengthened deliberative forums, inclusive development planning, and improved financial management. However, implementation faces significant challenges, including bureaucratic resistance to participatory governance, weak institutional capacity, limited public awareness, and corruption risks. These challenges highlight the need for institutional reform, ethical leadership, and greater community involvement. This article contributes by offering a holistic analysis of the potential and challenges of policies based on Islamic political values to achieve sustainable and accountable village development. It also provides theoretical contributions to the discourse on Islamic constitutionalism and practical guidance for improving rural governance.